PEMANFAATAN ABU KULIT BUAH KAPUK RANDU SEBAGAI ALTERNATIF BAHAN PENGEMBANG KUE - Nenik Yuniarti; Sulhadi Sulhadi; Teguh Darsono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Kapok tree (C. pentandra) is a plant that is commonly found in Indonesia. The skin of kapok fruit containing sodium substances can be utilized as raw material for making baking soda. The purpose of this study is to determine the increase in the volume of cakes owned by food developers. This research method by soaking the ashes of the skin in the air at least 12 hours. Soaked ashes of filtered ashes and evaporated water until temperature of 890 C until the result of baking soda solids. Baking soda testing was done on steamed brown dough. First, the brown dough is given 5 grams, volume is 722.5 cm3. Second, given 10 grams of baking soda, the volumes 1011.5 cm3. As much as 15 grams, the volume 1156 cm3. The provision of baking powder as a comparison is done by the same treatment. The first, given 5 grams of developers, resulting volume 722.5 cm3. Second, as much as 10 grams, the volume 1011.5 cm3. Third, as much as 15 grams, the volume 1156 cm3. From the above test, the addition of baked soda to brownie cake contains the same volume as the volume produced on the addition of baking powder. Keywords: Fruit leather ashes, baking soda